واقع تطبيق الجودة والتقويم الذاتي في مؤسسات التعليم العالي بولاية النيل الأبيض من وجهة نظر أعضاء هيئة التدريس 2019 - 2020م - د.مرتضىيونسبشير (White Nile Journal for Studies and Research, 2020)
The study aimed to find out the reality of the implementation of quality and self accreditation in the institutions of higher education in White Nile state. For the purpose of this study the researcher distributed a questionnaire with 51 indicators distributed over 7 standards. To ensure the correctness of performance the researcher tested the apparent reliability and self reliability. The sample of the study was selected from the research population that composed of university staff of (60) persons. For statistical analysis of the data the researcher used (SPSS) the statistical procedures of ministry of higher education. After the analysis of data the following results were found out 1. The reality of quality implementation in the institutions of higher education is good 2. The university infrastructure is weak 3. The quality of the members of staff is good and most staff member hold Ph. Ds. The study recommends the following: 1. More attention should be given to scientific research 2. To activate community participation in the institutions of higher education.